Measuring the Impact of Economic Openness on Unemployment Rates in Some Selected Middle Eastern Countries for the Period (2010-2020) - Maria Hamad Aziz; Twana Fadhil Salih (Zanco Journal of Humanity Sciences)
This study aims to show the impact of the openness of the economies of some countries in the Middle East on their unemployment rates, and to achieve this purpose, Panel models were used that mix time series data and cross-sectional data during the period 2010-2020, on a sample consisting of six countries from the selected Middle East region They are: Iraq, Turkey, Jordan, Iran, Armenia and Lebanon. The results obtained showed weak correlations between indicators of economic openness and unemployment on the one hand, openness to world trade has a weak negative significant effect on the unemployment rate represented by the ratio of foreign trade to GDP in part of the studied regressions on the other hand, and therefore it can be said that Trade openness was not a major determinant of unemployment in the Middle East region